Molecular Mechanisms of Selenium Mitigating Lead Toxicity in Chickens via Mitochondrial Pathway: Selenoproteins, Oxidative Stress, HSPs, and Apoptosis - Weichen Hong; Yuhao Liu; Jiatian Liang; Chunyu Jiang; Meijin Yu; Wei Sun; Bin Huang; Na Dong; Lu Kang; You Tang (Toxics, 2023)
Lead (Pb), a hazardous heavy metal, can damage the health of organisms. However, it is not clear whether Pb can damage chicken cerebellums and thalami. Selenium (Se), an essential nutrient for organisms, has a palliative effect on Pb poisoning in chickens. In our experiment, a model of chickens treated with Pb and Se alone and in combination was established to investigate the molecular mechanism of Se alleviating Pb-caused damage in both chicken cerebellums and thalami. Our morphological results indicated that Pb caused apoptotic lesions, such as mitochondrial and nuclear damage. Further, the anti-apoptotic gene Bcl-2 decreased; on the contrary, four pro-apoptotic genes (p53, Bax, Cyt c, and Caspase-3) increased under Pb treatment, meaning that Pb caused apoptosis via the p53-Cyt c-Caspase-3 pathway. Furthermore, we further demonstrated that Pb elevated four HSPs (HSP27, HSP40, HSP70, and HSP90), as well as HSP70 took part in the molecular mechanism of Pb-caused apoptosis. In addition, we found that Pb exposure led to oxidative stress via up-regulating the oxidant H2O2 and down-regulating four antioxidants (CAT, SOD, GST, and GPx). Moreover, Pb decreased three Se-containing factors (Txnrd1, Txnrd2, and Txnrd3), further confirming that Pb caused oxidative stress. Interestingly, Se supplementation reversed the above changes caused by Pb and alleviated Pb-induced oxidative stress and apoptosis. A time dependency was demonstrated for Bcl-2, Bax, and Cyt c in the cerebellums, as well as CAT, GPx, and p53 in the thalami of Pb-exposed chickens. HSP70 in cerebellums and HSP27 in thalami were more sensitive than those in thalami and cerebellums, respectively, under Pb exposure. Pb-induced apoptosis of thalami was more severe than cerebellums. In conclusion, after Pb treatment, Txnrds mediated oxidative stress, oxidative stress up-regulated HSPs, and finally, HSP70 triggered apoptosis. Se supplementation antagonized Pb-induced oxidative stress and apoptosis via the mitochondrial pathway and selenoproteins in chicken cerebellums and thalami. This study provides new information for the mechanism of environmental pollutant poisoning and the detoxification of Se on abiotic stress.